Intertextuality in the tales of Rabbi Nahman of Bratslav: a close reading of Sippurey Maʾasiyot - Schleicher, Marianne (Studies in the history of religions 0169-8834, 2010)
Until 1806, Rabbi Nahman of Bratslav (1772-1810) disseminated his thoughts on redemption through homilies. In 1806, however, Nahman chose the genre of tales as an additional and innovative means of religious discourse. This book draws upon the concept of "intertextuality" to explain how Nahman defines his theology of redemption